A Key to Home: Illuminating the Role of the SIM Card in Refugee Resettlement - Hingley, Liz (Imaginations)

(untitled) (York University, 2022)
This paper considers how creative research mediated by mobile devices might contribute to upending inherited notions of refugee powerlessness and passivity in galleries and museums. A collaborative project, undertaken in 2019, explored the significance of SIM cards in forging a sense of security, identity, and belonging for Syrian refugees on a resettlement program in the U.K. This “opening up” the “body” of the smartphone in the process of creating artworks reveals the urgent need for deeper appreciation of the meaning and materiality of personal digital ecosystems (Blanke & Pybus 2020) for refugees negotiating a sense of home.